KINERJA PENYULUH PERTANIAN LAPANG (PPL) PEREMPUAN DI KOTA METRO - Viantimala, Begem; Gs, Sumaryo (Lampung University)
The study intends to figure out performance female extension workers and to investigate its relation to the farmers group performance. The role of agriculture extension services has been very important to support the agriculture development.Â Metro City, which proclaimed as an agropolitan city, has nine male and eight female agriculture extension workers (PPL).Â Female agriculture extension workers contribute in agricultural development.Â Their responsibility is not different to those of male agricultural extension worker.Â Their performance can be measured by farmerâs group capability.Â There are many factors relate to female agricultural extension workerâs performance.Â The research shows that (1) the female agricultural extension workerâs performance is in medium category; (2) income and distance from home to the work place are correlated to the their performance; (3) farmerâs group capability was medium category; (4)Â farmers group performance are not related to their capability.